A Study Review On Coating For Intermediate Temperature Solid Oxide Fuel Cell (SOFC) And Low Temperature Sofc Using Electro-Phoretic Depositon (EPD) As Interonnect Coating Technique - Muhammad Amin; Azmi, Mohd Azham (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Solid Oxide Fuel Cell (SOFC) is considered by many developed countries as an alternative solution of energy in near future. The potential and promises shown by it has led to many developments of SOFC to maximize the productivity and durability. Different materials, design and fabrication technologies have been developed and tested to make it cost effective and stable. But the most advancement that have been made is the reduce of temperature of SOFC from high temperature to low temperature. This thesis is focused on the difference of temperature of SOFC, categorized into two, Intermediate Temperature SOFC (IT-SOFC) and Low Temperature SOFC(LT-SOFC). While both has the same interconnect coating technique, the characterization of both type of SOFC are different. The characterization of SOFC can be seen under three different tests, which are Xray Diffraction Analysis (XRD), Coating thickness test via Scanning Electron Microscope (SEM) and a test using Area Specific Resistance (ASR) via Electro Impedance Spectroscopy (EIS).